Endovascular therapy for middle cerebral artery M2 segment occlusion: subanalyses of RESCUE-Japan Registry 2. (9th March 2019) - Miura, Masatomo; Yoshimura, Shinichi; Sakai, Nobuyuki; Yamagami, Hiroshi; Uchida, Kazutaka; Nagao, Yoichiro; Morimoto, Takeshi
Abstract : Objective: To compare the efficacy of endovascular therapy (EVT) with that of medical treatment in 'real-world 'patients with M2 occlusion. Methods: This was a post hoc analysis of the Recovery by Endovascular Salvage for Cerebral Ultra-acute Embolism Japan Registry 2. Among 2420 patients in the registry, we evaluated patients with isolated M2 occlusion and those with functional independence before the stroke. Multivariable logistic regression analysis was used to evaluate and compare clinical outcomes between EVT and medical treatment. Additional propensity score-matched (PSM) analyses were performed. We performed subgroup analyses of the primary outcome (modified Rankin Scale score 0–2 at 90 days) using forest plots of treatment effects. Results: Overall, 372 patients with M2 occlusion (n=184 EVT; n=188, medical treatment) were evaluated. The EVT group had a higher baseline National Institutes of Health Stroke Scale score (median (IQR), 15 [9–19] vs 10 [5–16]) and earlier onset to hospital door time (110 [50–258] vs 150 [60–343] min) than the medical treatment group. After adjustment, EVT was significantly associated with higher odds of primary outcome (adjusted OR=2.09; 95% CI 1.26 to 3.47) and lower odds of mortality at 90 days (adjusted OR= 0.27; 95% CI 0.08 to 0.93). After PSM analyses (184 patients were 1:1 matched with each group), EVT was effective and safe relative to medical treatment. Effects favoring EVT were present in several subgroups of interest. Conclusion: In patients with M2 occlusion, our registry suggests that EVT is effective and safe.